THU0166 Comparison of the risk of comorbidities between patients with rheumatoid arthritis and diabetes mellitus using japanese health insurance database. (15th June 2017) - Sakai, R; Kasai, S; Tsutsumino, M; Yamanaka, H; Miyasaka, N; Harigai, M
Abstract : Background: Patients with rheumatoid arthritis (RA) have a higher risk of comorbidities such as infections 1, cardiovascular diseases 2, and fractures 3 than general population. To understand the risk of these comorbidities in RA more precisely, it is needed to compare the risk between RA and other chronic diseases. A Dutch study 4 showed that patients with RA had comparable risk of cardiovascular diseases to diabetes mellitus (DM). Because of possible racial or ethnic difference of risks of comorbidities, it is warranted to compare the risk between RA and DM in Asian countries. Objectives: To compare risk of hospitalized infections (HIs), cardiovascular diseases and stroke (CVDs), and fractures between RA and DM cases using Japanese health insurance database. Methods: This retrospective longitudinal population-based study was conducted using claims data provided by the Japan Medical Data Center Co., Ltd. We defined individuals as RA cases if they met all of the following: 1) had at least 6 months of continuous enrollment in the health insurance database; 2) had at least one RA diagnostic code and at least one prescription of disease-modifying antirheumatic drugs between January 2005 and December 2013; and 3) were ≥50 years old (RA group, n=3, 607). Among individuals who met above criteria 1) and had at least DM diagnostic code and at least one prescription of drugs for DM, but did not meet 2), we selected age- (±5 years), gender-, calendar year of the observation start, and observation length-matched DM cases at 1:3 ratio (RA: DM) (DM group, n=10, 821). Each comorbidity was defined as follows: HIs, at least one ICD10 code and one prescription of drugs for infections with hospitalization; CVDs, at least one ICD10 code and one prescription of drugs or medical procedures for CVDs with hospitalization; fractures, at least one ICD10 code for fractures. We calculated incidence rates (IR) with 95% confidence interval (CI) of each comorbidity in the two groups up to 10 years and adjusted odds ratio (OR) of RA compared with DM for each comorbidity using generalized estimating equation. Results: The median age was 58, and 75.1% were female in the both groups. The IR [95% CI] of HIs, CVDs, and fractures was 2.8 [2.5–3.2]/100 patient years (PY), 9.2 [7.4–11.4]/1, 000 PY, 16.7 [14.2–19.6]/1, 000 PY in the RA group, 2.8 [2.6–3.0]/100PY, 26.3 [24.4–28.3]/1, 000PY, 10.3 [9.1–11.6]/1, 000PY in the DM group respectively. The OR [95% CI] of RA (vs. DM) for HIs, CVDs, fractures was 0.9 [0.8–1.1], 0.4 [0.3–0.6], 1.3 [1.0–1.7] after adjusting for baseline characteristics. Conclusions: This study revealed that patients with RA had significantly lower risk of CVDs than and similar risk of HIs and fractures to those with DM using health insurance database for the first time in Asia. References: Arthritis Rheum, 2002;46:2287–93. Ann Rheum Dis, 2012:71:1524–29. Arthritis Res Ther, 2010;12:R154. Arthritis Rheum, 2009;61:1571–9. Acknowledgements: This work was supported by the research grant from the Ministry of Health, Labour, and Welfare, Japan. Disclosure of Interest: R. Sakai Grant/research support from: Ayumi Pharmaceutical Co., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Nippon Kayaku Co., Ltd., Taisho Toyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., and Teijin Pharma Ltd., Bristol-Meyers Squibb, S. Kasai: None declared, M. Tsutsumino Grant/research support from: Ayumi Pharmaceutical Co., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Nippon Kayaku Co., Ltd., Taisho Toyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., and Teijin Pharma Ltd., H. Yamanaka Grant/research support from: Chugai Pharmaceutical Co. Ltd., Astellas Pharma Inc., Bristol-Meyers Squibb, AbbVie Japan Co. Ltd., Daiichi-Sankyo, Mitsubishi-Tanabe Pharma Corp., Takeda Pharmaceutical Co. Ltd., UCB Japan., Consultant for: Chugai Pharmaceutical Co. Ltd., Astellas, Bristol-Meyers Squibb, AbbVie Japan Co. Ltd., Daiichi-Sankyo, Mitsubishi-Tanabe Pharma Corp., Takeda Pharmaceutical Co. Ltd., UCB Japan., Speakers bureau: Chugai Pharmaceutical Co. Ltd., Astellas, Bristol-Meyers Squibb, AbbVie Japan Co. Ltd., Daiichi-Sankyo, Mitsubishi-Tanabe Pharma Corp., Takeda Pharmaceutical Co. Ltd., UCB Japan., N. Miyasaka: None declared, M. Harigai Grant/research support from: Ayumi Pharmaceutical Co., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Nippon Kayaku Co., Ltd., Taisho Toyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Mitsubishi Tanabe Pharma Co., and Teijin Pharma Ltd., Eisai,